Involvement in Multiple Race Events Among International Para and Non-disabled Swimmers - Schipman, Julien; Saulière, Guillaume; Le Toquin, Bryan; Marc, Andy; Forstmann, Nicolas; Toussaint, Jean-François; Sedeaud, Adrien (Frontiers in Sports and Active Living, 2021)
International elite Para swimmers form a large portion of the overall multi-medalist winning population. For the highest performing Para swimmers, world class performances were achieved across different strokes. The aim of this study was to quantify the level of involvement across different events and to examine this in relation to the level of performance. The performances in swimming speed of the top 100 females and males for both Para- and non-disabled swimmers were collected in 11 race events between 2009 and 2019 (4400 performances for 307 Para females and 365 Para males, 605 non-disabled females and 715 non-disabled males). We tallied the number of events in which each swimmer was involved. Swimmers were grouped according to the total number of race events in which they participated. Then the association between involvement and level of performance was investigated. Para swimmers with impairment from classes 7 to 14 were involved in a range of race events across different strokes. The most common combination for both Para and non-disabled athletes was over similarly distanced races of the same stroke (50m and 100m freestyle). The more race events in which para-swimmers involved, the higher the level of performance that was achieved. This trend can partially be explained by the less concentrated competition pool for Para swimmers compared to able-bodied swimmers. Para swimmers with minimal and no physical impairment perform in multiple race events more often than able-bodied swimmers. Fewer Para swimmers at the international level and a less concentrated competition pool could explain these differences.